Asian monsoon dynamics and sediment transport in SE Asia. (15th June 2020) - Clift, Peter D.
Highlights: Periods of strong monsoon result in reworking of flood plain sediments. Sediment deposited during times of heavy summer rain is more altered than at other times. Chemical weathering does not react on millennial time scales to climate change. Strong monsoon increases erosion of bedrock over million-year time scales. Abstract: The Asian monsoon is the dominant climatic phenomenon in Southeast Asia, responsible for most of the regional precipitation. As well as tectonics, climate is well recognized as a primary control on erosion and the transport of sediment to the ocean. Sediment records from the South China Sea show that strong monsoons are associated with intensified reworking of pre-existing floodplain sediments over millennial timescales. Strong monsoons result in deposition of more altered material that is also delivered at higher rates than during more arid times. Millennial-scale changes in monsoon strength result in changes in the weathering regime but not fast enough to account for the changes seen in the sediments preserved in Asian deltas. Instead monsoon modulated recycling dominates. Over longer time periods (>10 6 y) strengthening of the monsoon is linked to faster bedrock erosion and increased sediment flux of the ocean. Although this also has an effect on chemical weathering, on long time periods the monsoon is seen to be subsidiary to the effects of global cooling at least since the middle Miocene.